Edukasi Persiapan Kolam Sebelum Penebaran Benih Lele Pada Kelompok Pembudidaya Ikan (Pokdakan) Tunas Melati Kecamatan Tebas - Izhar Amirul Haq; Dewi Merdekawat; Indra Mahyudi; Beryaldi Agam; Debby Urabi; Maryono; Jordi; Nurul Fatimah Yunita; Saifullah (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This community service activity aimed to improve the knowledge and skills of fish farmer group members in preparing ponds prior to catfish seed stocking to support successful cultivation during the initial rearing phase. The activity was conducted on December 20, 2025, in Tebas Sungai Village, Tebas District, Sambas Regency, in collaboration with the Tunas Melati Fish Farmer Group (Pokdakan), involving 15 participants. The implementation method employed an educational-participatory approach through classroom-based counseling, discussions, demonstrations, and hands-on pond preparation practices on eight culture ponds measuring 4 × 4 meters each.The practical activities included pond cleaning, salt application as a simple sanitation method, initial water filling, water drainage, pond drying, final water filling, and preparation of ponds for catfish seed stocking. Evaluation was conducted through observation of participant involvement, oral discussions, and participants’ ability to explain the pond preparation procedures after the activity.The results showed that participants understood the importance of preparing the culture medium before seed stocking and were able to follow the pond preparation procedures systematically. The activity was implemented smoothly without significant obstacles and contributed to enhancing the capacity of group members in managing catfish culture media. Practice-based education was found to be effective in improving participants’ understanding of pond readiness as a supporting factor for the successful initial adaptation of catfish seed.